Role of Molecular Biomarkers in the Diagnosis of Invasive Fungal Diseases in Children - Huppler, Anna R (J Pediatric Infect Dis Soc, 2017)
Invasive fungal diseases are important clinical problems that are often complicated by severe illness and therefore the inability to use invasive measures to definitively diagnose the disease. Tests for a range of fungal biomarkers that do not require an invasive sample-collection procedure have been incorporated into adult clinical practice, but pediatric data and pediatric-specific recommendations for some of these diagnostic tools are lacking. In this review, we summarize the published literature and contemporary strategies for using the biomarkers galactomannan, (1→3)-β-d-glucan, Candida mannan antigen and anti-mannan antibody, and fungal polymerase chain reaction for diagnosing invasive fungal disease in children. Data on biomarker use in neonates and children with cancer, history of hematopoietic stem cell transplant, or primary immunodeficiency are included. Fungal biomarker tests performed on blood, other body fluids, or tissue specimens represent promising adjuncts to the diagnostic armamentarium in populations with a high prevalence of invasive fungal disease, but substantial gaps exist in the correct use and interpretation of these diagnostic tools in pediatric patients.